Round robin testing initiative for fiber reinforced polymer (FRP) reinforcement - Palmieri, A. (2011)
An international Round Robin Testing (RRT) programme on FRP reinforcement was conducted within the framework of the Marie Curie Research Training Network, ENCORE, and with the support of Task Group 9.3 of the International Federation for Structural Concrete (fib). Eleven laboratories and six manufacturers and suppliers participated in this exercise. As part of this extensive experimental endeavour, one or more of the following tests were performed by the participating laboratories: 1) tensile tests on FRP bars and strips; 2) tensile tests on FRP laminates; 3) double bond shear tests on FRP laminates (Externally Bonded Reinforcement, EBR) and FRP bars/strip (Near Surface Mounted reinforcement, NSM). This paper will discusses the results of the RRT initiative, among which the experimental results of bond tests on concrete specimens strengthened with EBR and NSM FRP.